Genetics Poly Cystic Ovary Syndrome - Bahadori, Atekeh; Khazamipour, Afrouz; D.Farhud, Dariush (Asian Pacific Journal of Cancer Biology, 2016)
Background: Polycystic ovarian syndrome is a complicated hereditary disorder which does not have specific reason and 6-10% of women at fertility age are involved. In other word we can say that this syndrome is a familial hereditary syndrome which developed with combination of environmental and genetic factors. Polycystic ovarian syndrome (PCOS) is related to cardiovascular diseases and has psychological and neurological effects on life quality as well as uterine and breast cancers. The main criteria for diagnosis of polycystic ovarian syndrome are chronic anovulation and hyperandogenism and the sub-criteria are insulin resistance, hirsutism and obesity onset at menarche age, anovulation alternatively is associated with increased testosterone level and DHEA-S. The cause of polycystic ovarian syndrome (PCO) is unknown, but it could be the result of complex genetic factors which are evident at puberty onset, also hereditary and non-hereditary factors could be the cause of polycystic ovarian syndrome (PCO) pheno ype. In many women with polycystic ovarian syndrome, the insulin level is high. It seems that high levels of insulin increase androgens production. High levels of androgens can cause acne, supernumerary hair growth, weight gain, and ovulation problem. Conclusion: Early diagnosis and treatment of polycystic ovarian syndrome could help to reduce long-term complications such as diabetes type II, high blood pressure, heart disease and stroke.